Slaughtering by ahli kitab and reciting Basmalah in slaughtering / Dania Qistina Aisy Rosmaily … [et al.] - Rosmaily, Dania Qistina Aisy; Hassan, Norsafia; Mohd Fisal, Nur Syafiqah; Mohd Yusoff, Nur Aisyah Atiqah; Ibrahim, Safurah (2023)
The concept of slaughter in Islam or Zabiha has laid down guidelines in the slaughter of animals well and thoroughly. In-depth knowledge of the method of slaughtering according to Sharia is very important because it is closely related to spiritual and health factors. Mawsu'ah al-fiqhiyyah defines al-dhaba'ih as having three meanings which are cutting in the throat which is between the lower neck and two veins in the neck, cutting in the throat or below the neck and anything capable of injuring an animal whether cutting in the neck or under the neck of an animal that can be controlled or remove the spirit of an animal that cannot be controlled by wounding any part of the animal's body. The wisdom of slaughter from the point of view of Sharia and science is to be able to distinguish between halal meat and haram meat and speed up the death process of slaughtered animals. Next, avoid diseases found in animals because the toxins and bacteria found in animals have been removed.